Uranium mining: post-closure land uses – a personal global review - Waggitt, P.W. (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
The mining industry has a long and chequered reputation when it comes to remediation, closure and post-mining land use. There are, sadly, too many poor examples around the world of abandoned mines and remediation projects that have failed to live up to expectations. Modern society has great expectations and high standards that they expect to see enforced when new mining projects are being assessed for development. It is therefore important for the global mining industry to be able to demonstrate that there are examples of useful post-closure uses for former mining sites. In the case of uranium mining, which carries the additional ‘stigma’ of radioactivity it is even more important to show that mining, even uranium mining, need not be a one-time user of land. This paper describes a selection of former uranium mining sites from around the world where remediation has been completed, or is ongoing, and post-mining land use has been established or is nearing completion. The examples are drawn from Europe, the United States of America and Australia.